Controlling Stormwater Runoff That Limits Water Availability and Dryland Crop Productivity - Baumhardt, R. Louis; Dockal, Justin R.; Johnson, Grant L.; Brauer, David K.; Schwartz, Robert C. (Frontiers in Sustainable Food Systems, 2020)
Continued pumping for irrigation from the non-recharging Ogallala aquifer in Kansas and Texas is unsustainable. Reducing risks for dryland wheat (Triticum aestivum L) and sorghum [Sorghum bicolor (L.) Moench] production, which depends exclusively on precipitation to meet water demand is critical for future adoption. Stormwater runoff reduces the amount of precipitation available to crops, but management practices to minimize runoff concomitantly increase the opportunity time for infiltration and improve precipitation storage as soil water for crop use. Our objectives in this study were to evaluate tillage, slope and the effects of contour or with-slope farming on runoff, soil water at planting, and the growth and yield of wheat and sorghum grown in the 3 years wheat-sorghum-fallow (WSF) rotation. Long-term, 1983 to present, runoff was measured from gauged terraced and contour farmed fields managed in the WSF rotation with no-tillage (NT) or stubble-mulch (SM) tillage. We found significantly greater mean cumulative runoff during fallow for NT than for SM but only for the 1.8% terrace slopes., The corresponding soil water with NT increased by a significant 27 mm over SM due to reduced evaporation but generally did not differ due to slope. Wheat yield decreased significantly as slope decreased from 1.8 to 1.2% but exhibited no yield response tillage. In contrast, grain sorghum yields were greater with NT than SM tillage residue management. Farming along the contour or slope manifested no differences in soil water, crop grain yield, or water use; however, they did increased significantly with no tillage for sorghum but not wheat. We conclude that management of tillage was more effective than slope effects in increasing water availability to crops because of evaporation reduction with crop residue.